Mukositis Oral dan Kualitas Hidup Spesifik–Mukositis Oral pada Anak Kanker yang Menjalani Kemoterapi: Oral mucositis and quality of life-specific Oral mucositis in children Cancer Patients Undergoing Chemotherapy - Dwi Novrianda; Yulastri Arif (Fakultas Keperawatan Universitas Andalas, 2017)
One of the side effects generally occur during chemotherapy is oral mucositis. Disorders due to oral mucositis often affects the psychological and decreased quality of life of children. Therefore, It is important to determine the relationship of oral mucositis in cancer patients undergoing chemotherapy and quality of life related to oral mucositis. This research was descriptive analytic with cross sectional approach. Respondents in this study were children with cancer who were undergoing chemotherapy in Chronic Ward Pediatric Inpatient RSUP Dr. M. Djamil Padang. The strategy used in determining the sample was consecutive sampling amounted to 132 people. Data were collected through questionnaires that Oral Mucositis Daily Questionnaire (OMDQ) and Oral Mucositis-specific Quality of Life (OMQoL). The results showed an average of 6.55 years old respondents, the majority of the male sex, and had been diagnosed with acute lymphocytic leukemia. 40% Respondents had experienced severe oral mucositis (a score of 2, 3, and 4) and have mild to severe limited activity primarily eating, drinking and swallowing. The average total score of the quality of life specific-oral mucositis was 58.61. Subscale diet and swallowing occupy the lowest scoring average and below the total score were 55.00 and 55.75. There were no significant differences quality of life specific-oral mucositis between mild and severe mucositis (p> 0.05). It is expected the professional nurse can identify conditions early oral mucous membrane of cancer patients and evaluate the implementation of oral mucositis intervention through-specific quality of life assessment of oral mucositis.